การคัดกรองฤทธิ์ต้านแบคทีเรียของเอนโดไฟต์ที่แยกได้จากต้นข้าว - รัตนาเกียรติ์ สกุลรัตน์; ป้องปาน วัชรพงษ์; อยู่พร้อม รัตนาพร (Thai Journal of Science and Technology, 2017)
บทคัดย่อ เอนโดไฟต์คือจุลินทรีย์ที่อาศัยในเนื้อเยื่อพืชโดยไม่ก่อโรค เป็นแหล่งผลิตสารสำคัญในธรรมชาติที่พัฒนาเป็นยาใหม่ได้ ข้าวเป็นพืชเศรษฐกิจที่สำคัญของไทย เอนโดไฟต์จากข้าวสามารถเป็นแหล่งที่ดีในการพัฒนาเป็นยาใหม่สำหรับรักษาโรค ซึ่งรวมถึงยาปฏิชีวนะ วัตถุประสงค์ของการศึกษานี้เพื่อแยกและศึกษาฤทธิ์ในการต้านแบคทีเรีย Staphylococcus aureus, methicillin-resistant Staphylococcus aureus, Bacillus subtilis, Escherichia coli และ Pseudomonas aeruginosa ของเอนโดไฟต์ที่พบในราก ลำต้น และใบของต้นข้าว โดยแยกเอนโดไฟต์มาจากต้นข้าว 2 บริเวณ เพาะเลี้ยงแล้วสกัดน้ำเลี้ยงเชื้อด้วยตัวทำละลายเอทานอล ความเข้มข้น 70 เปอร์เซ็นต์ นำมาทดสอบฤทธิ์ต้านแบคทีเรียด้วยวิธี agar well diffusion และหาค่าความเข้มข้นต่ำสุดในการฆ่าแบคทีเรีย (MBC) ด้วยวิธี broth-macrodilution ในการศึกษานี้แยกเอนโดไฟต์จากต้นข้าวได้ 44 ไอโซเลต จากการคัดกรองเบื้องต้นพบตัวอย่างที่มีฤทธิ์ต้านแบคทีเรีย 27 ไอโซเลต (ร้อยละ 61.63) คัดเลือกเอนโดไฟต์ทดสอบในขั้นต่อไป 3 ไอโซเลต คือ S133, S232 และ R214 โดยสารสกัดน้ำเลี้ยงเชื้อของเอนโดไฟต์ทั้งสามชนิดมีฤทธิ์ต้านแบคทีเรียทดสอบทุกชนิด ให้โซนใสระหว่าง 7.09 ถึง 13.25 มิลลิเมตร ค่า MBC ระหว่าง 16.67 ถึงมากกว่า 33.33 มิลลิกรัมต่อมิลลิลิตร แสดงให้เห็นว่าเอนโดไฟต์จากต้นข้าวเป็นอีกแหล่งหนึ่งของสารต้านจุลชีพที่สามารถพัฒนาได้ต่อไป คำสำคัญ : ข้าว; เอนโดไฟต์; ฤทธิ์ต้านแบคทีเรีย Abstract Endophytes are microorganisms that live inside the living plant tissues without causing any apparent disease symptoms in the host. The endophytes are known to produce various natural products, which could be a consistent and successful source of drugs. Rice (Oryza sativa L.) is the most important crop in Thailand. Endophytes from rice could be the great sources of new therapeutic compounds including antibiotics. The purpose of this study was to isolate endophytes from roots, leaves and stems of rice plant, and investigate their antibacterial activity against Staphylococcus aureus, methicillin-resistant Staphylococcus aureus, Bacillus subtilis, Escherichia coli and Pseudomonas aeruginosa. The endophytes were isolated from the plants collected from 2 areas, and ethanolic extracts of culture medium were screened for antibacterial activity using agar well diffusion method. Minimum bactericidal concentration (MBC) was investigated using broth-macrodilution method. The screening of antibacterial activity was found in 27 isolates (61.63 %), out of all 44 isolates. Three isolates with high activity were selected for further investigation including S133, S232 and R214. Inhibitory effects were observed in all 3 endophytes against tested bacteria with clear zone of 7.09 to 13.25 mm. and MBC 16.67 to more than 33.33 mg/ml. These indicated that endophytes isolated from rice plant could be a promising source of antimicrobial substances. Keywords: Oryza sativa L.; endophyte; antibacterial activity